Exclusion and Discrimination in the Labor Market - Das, Maitreyi Bordia (World Bank, Washington, DC, 2014)
The frameworks developed in this paper are based on a review of the literature on processes of discrimination and the norms and attitudes that accompany them. Intended as a background paper to the World Development Report 2013 this paper will also feed into the Social Inclusion Flagship Report by the Social Development Department at the World Bank. It is divided into six sections. This section one is an introduction to the objectives and provides the context for this work. Section two is a brief discussion of the conceptual underpinnings and measurement of labor market discrimination from a cross-disciplinary perspective. Section three lays out a typology of processes of discrimination, while section four is a discussion of the mechanisms of discrimination and the ways in which candidates are screened. Section five addresses the question of how discriminated groups react to discrimination. The final section addresses some of the ways in which occupational and labor market mobility is possible for disadvantaged groups and what policy implications it could have.